The Interplay Of Positivism And Pedagogical Assessment in Shaping Teacher Performance - Kamalasia Rio Nita; Mahdum Mahdum; Jimmy Copiriady; Isjoni Isjoni (Mudir: Jurnal Manajemen Pendidikan, 2026)
This paper explores the intricate relationship between positivism, pedagogical assessment, and teacher performance within the contemporary Indonesian educational landscape. Drawing upon a deep philosophical analysis of positivism, from its foundational tenets by Auguste Comte to its modern interpretations and critiques, this study integrates empirical evidence from Indonesia to provide a comprehensive understanding. The article delves into how positivistic approaches have shaped pedagogical assessment methodologies, influencing the evaluation of teacher performance in Indonesia. Furthermore, it examines the implications of these approaches for fostering Higher Order Thinking Skills (HOTS) among students, considering the unique cultural and educational context of Indonesia, including the influence of Pancasila and local values. Through a synthesis of theoretical frameworks and empirical findings, this paper aims to offer insights into optimizing teacher performance assessment to promote a more holistic and effective educational system in Indonesia. Visual elements, including a diagram illustrating the conceptual framework, a relevant image depicting an Indonesian classroom, and a comparative table of positivism and post-positivism, are integrated to enhance understanding and provide a multi-faceted perspective.